Pioneer Business in Vegetable Sate Lilit Products (Lilitveg) Among the Community - rafi eldri (Business Management, 2026)
Changes in consumer behavior toward healthier and more sustainable foods have led to increased interest in plant-based foods. This situation opens up opportunities for innovation in traditional foods, one of which is through the Sate Lilit Nabati product called LilitVeg. This study aims to analyze market, marketing, production, organizational, and financial aspects as the basis for planning a start-up business for the Sate Lilit Nabati product. This study uses a descriptive approach in preparing the business plan (business plan) based on analysis of market conditions, consumer segmentation, marketing strategy, production planning, SWOT analysis, and business feasibility calculations. The results of the study indicate that LilitVeg has good market opportunities because it is supported by the increasing trend of plant-based food consumption, the high use of social media as a promotional tool, and public interest in healthier traditional food innovations. The main target market is consumers who are concerned about health and actively use digital media. The marketing strategy is carried out through Instagram, collaboration with food influencers, and education about the benefits of plant-based foods. The product's advantage is the use of plant-based ingredients with a distinctive Balinese flavor through basa genep seasoning, distinguishing it from similar products. Based on the analysis, the LilitVeg startup has good prospects for development as an innovative culinary venture focused on consumer needs, sustainability, and the preservation of traditional culinary traditions.